Dampak Perilaku Judi Online terhadap Kehidupan Sosial dan Akademik Siswa SMA di Kabupaten Semarang: Penelitian Deskriptif Kualitatif - Muhammad Aflahul Anam; AIhan Abizar Fardhan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to describe the impact of online gambling behavior on the social and academic lives of senior high school students in Semarang Regency. The increasing involvement of adolescents in online gambling has become a serious concern, as it affects not only individual psychological conditions but also social relationships and academic performance. This research employed a qualitative approach using a phenomenological design to understand the subjective experiences of students involved in online gambling activities. Data were collected through semi-structured interviews with five eleventh-grade high school students selected using purposive sampling based on their active participation in online gambling. Data were analyzed using the Miles and Huberman interactive model through data reduction, data display, and conclusion drawing, with validity ensured through source triangulation and member checking. The findings reveal that student involvement in online gambling was shaped by peer social environments, social media exposure, and initial winning experiences that triggered addictive behavioral patterns. Social impacts identified include decreased quality of family communication, increased dishonesty, interpersonal conflicts, and tendencies toward social withdrawal. In the academic domain, students experienced reduced learning concentration, delayed task submission, declining grades, and diminished classroom participation. Psychological impacts were also identified, including stress, anxiety, guilt, and difficulty controlling gambling urges. This study contributes to deepening the understanding of online gambling's multidimensional impacts on adolescents and underscores the importance of family, school, and educational policy engagement in prevention and intervention efforts.